On the subgenus Eurysunius Reitter of Turkey VII. Four new species from central Anatolia, and additional records (Coleoptera: Staphylinidae: Paederinae, Astenus) - Anlaş, Si̇nan (Zootaxa, 2021)
In the study, four new species of Astenus (Eurysunius) Dejean (Coleoptera: Staphylinidae: Paederinae) are described and illustrated from central Anatolia, in Turkey, and distinguished from related consubgeners: Astenus veyseli Anlaş, sp. n. (Sivas province), A. gultekini Anlaş, sp. n. (Kırıkkale province), A. kirani Anlaş, sp. n. (Sivas province) and A. neseti Anlaş, sp. n. (Kırşehir province). A key to Turkish species of Eurysunius is provided. The distributions of 22 species in Turkey are mapped.